Suspended sediment transport in coastal zone by tidal flow. Part I: Models of SPM vertical distribution - S. M., Anttsyferov; T . M., Akivis (Vietnam Journal of Mechanics, 2004)
The aim of the study is to develop methods for prediction of the vertical distribution of characteristics of sand and aleurite sediment suspended by tidal flow for the averaging time either divisible by tidal period (the first order model) or much less than it is (the second order one). The bottom is assumed to be erodible with possible formation of ripples. Part I: The theoretical and laboratory study of steady flow with suspension is used to develop the solution. The concentration field of heterogeneous sediment is considered as a sum of those of homogeneous groups of particles (fractions) moving under the same regulations. In the first order model, the hydrodynamical characteristics of the tidal flow are represented by their constant effective values. In the second order model the tidal flow is represented by the series of consecutive steady states (steps).